2005
DOI: 10.1176/appi.ajp.162.4.667
|View full text |Cite
|
Sign up to set email alerts
|

Conversion From Mild Cognitive Impairment to Probable Alzheimer’s Disease Predicted by Brain Magnetic Resonance Spectroscopy

Abstract: MRS of the brain performed on patients with mild cognitive impairment is a valuable tool in predicting conversion to probable Alzheimer's disease. Occipital values were more reliable than hippocampal values in this prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(71 citation statements)
references
References 35 publications
4
65
1
1
Order By: Relevance
“…These data confirmed previous evidence suggesting that decreased NAA/Cr levels predict future conversion to AD in subjects with MCI [26,86]. It was recently reported that while there were no differences in NAA/Cr, Cho/Cr and mI/Cr at baseline between stable MCI and MCI who converted to AD after a median follow-up period of thirteen months, the annualized rate of change in Cho/Cr ratio was greater in stable MCI compared to converter MCI and cognitively normal controls, suggesting a possible compensatory mechanism in stable MCI [61].…”
Section: Predictors Of Progression Of MCI To Dementiasupporting
confidence: 91%
“…These data confirmed previous evidence suggesting that decreased NAA/Cr levels predict future conversion to AD in subjects with MCI [26,86]. It was recently reported that while there were no differences in NAA/Cr, Cho/Cr and mI/Cr at baseline between stable MCI and MCI who converted to AD after a median follow-up period of thirteen months, the annualized rate of change in Cho/Cr ratio was greater in stable MCI compared to converter MCI and cognitively normal controls, suggesting a possible compensatory mechanism in stable MCI [61].…”
Section: Predictors Of Progression Of MCI To Dementiasupporting
confidence: 91%
“…MRSI could also help in the prediction from MCI to dementia. Some studies have reported lower NAA/Cr [153][154][155][156][157] and higher Cho/Cr [158] levels in several brain regions in MCI patients who developed dementia than stable MCI subjects. Nevertheless, some disagree with these findings [159,160] so further research is needed to verify MRSI's predictability from MCI to AD.…”
Section: Magnetic Resonance Spectroscopic Imaging (Mrsi)mentioning
confidence: 99%
“…The neuronal integrity marker N-acetylaspartartate (NAA) and NAA/creatine (Cr) levels on 1 H MRS are lower in AD compared to normal elderly subjects [46], and decreased NAA/ Cr levels predict future conversion to AD in aMCI [6,30,34]. Furthermore, decreased NAA levels in other neurological disorders such as epilepsy [15], head trauma [3], and multiple sclerosis [25,36] may recover after successful treatment.…”
Section: Introductionmentioning
confidence: 99%